Classe hospitalar: a importância do acompanhamento pedagógico para crianças e adolescentes - Sandroni, Giuseppina Antonia (2011)
Pedagogical and play activities promote social, cognitive and affective development in children and adolescents; they also contribute towards healing process and alleviate pain and suffering in students who have been hospitalized and cannot participate in their social environments and school. Based on this assumption, this study aimed at investigating which pedagogical activities are directed to hospitalized children and adolescents. This is a qualitative and exploratory research in which data were collected through a semi-structured survey. The participants were the companions of the users of pediatrics, health professionals working at the pediatric unit physicist, nurses, psychologist, social assistant and the regional supervisor of special education. Data were analyzed based on meaning units. The results are suggestive that there is a lack of knowledge on the benefits of pedagogical and play activity in hospital environments. Factors such as the lack of appropriate place for the activities, the lack of professionals to perform the activities and the user s unawareness of their right to hospital classroom, contribute for keeping this population excluded from daily school routine. Considering that being hospitalized represents radical changes to children and adolescents, since playing and learning are turned into a painful and uncertain routine, the results indicate conditions for installing hospital classrooms, which should be provided by Special Education. Pedagogical and play activities, allied to a humanized hospital environment, would contribute to new expectations and hopes, and to the learning process in children and adolescents who need to overcome the hospitalization barrier.